International financial management - Madura, Jeff; Madura, Jeff (Andover, Massachusetts. Cengage Learning, 2023)
Provides a comprehensive examination of financial practices and strategies in a global setting. It covers the functioning of international financial markets, risk management techniques, and the financial decision-making processes of multinational corporations. The book addresses the complexities of global investments, currency fluctuations, and economic factors influencing international finance, equipping readers with the knowledge to effectively manage financial operations across borders.
Part I. The international financial environment1. Multinational financial management: an overview2. International trade, measurement and theories3. International financial markets and portfolio investment4. EthicsPart II. Exchange rate behaviour5. Exchange rate changes 6. Exchange rate history and the role of governments7. Forecasting exchange rates8. International arbitrage and covered interest rate parity9. Relationships between inflation, interest rates and exchange ratesPart III. Exchange rate risk management10. Measuring exposure to exchange rate fluctuations11. Market insurance: currency derivatives12. Non-market methods of transaction management13. Economic and translation exposure managementPart IV. Long-term asset and liability management14. Foreign direct investment15. Country risk analysis16. Long-term financingPart V. Short-term asset and liability management17. Financing international trade18. Short-term financing19. International cash management20. Concluding commentsAppendix A: Answers to self-test questionsAppendix B: Maths and statistics supportOnline additional reading1. Multinational restructuring2. Multinational cost of capital and capital structure3. Multinational capital budgeting
Strategic management of financial decisions in a global context, addressing risks and opportunities in international markets.
18 and above
Keywords: Entreprises multinationales Finances; Foreign exchange; International finance